Geophysical Characterization of Disturbances in the Phosphate Series of the OuladAbdoun, Morocco: Relationship with Atlasictectonics - Zerouali E.; Wafik A.; Najine A.; Radouani F.; Alaoui M.; Housni F. E. (European Scientific Journal, ESJ, 2020)
The sedimentary phosphates series from the Upper Maastricht to the Lutetion of the OuladAbdoun sedimentary basin is almost identical at the basin-scale. It is made up by alternation of either phosphate or non-phosphate sub-horizontal levels. The series was characterized by rhythmic sedimentation under the form of successive elementary sequences. On the other hand, the series of SidiChennaneis distinguished by the presence of local disturbances defined by the miners under the term "dérangements". These "dérangements", which are less frequent at other mining sites (MEA Lahrech, El Hlassa, Point A), are a notable problem during extraction and remain a real obstacle at phosphate mining sites. The morphology of these "dérangements" is almost subcircular to subconical sinkholes and chaotic bodies of anarchical materials. They are fontis type paleokarsts, it is an amalgam of highly altered yellowish brecciated rusty material whose lithological nature reflects that of the surrounding series. They also reflect endokarst siliceous and ferruginous neoformedfacies in the empty spaces of the palaeokarst. The origin of the palaeokarstshasbeen linked to the presence of NE-SW trend faults that have favoured the alteration and dissolution of the gypsum and chalk facies of the Senonian. The regular spatial distribution of these fontisis well related to the regionalAtlasictectonics. This study aims to investigate these problems in its geological aspect, in order to characterize and understand their origin. The purpose of this work isto compare the results obtained by electric tomography, gravimetry and lineament mapping and match them with geological data to draw a meaningful conclusion on the existence of these disturbances and their spatial distribution in relation to tectonic.